Students’ Anxiety in Learning English Writing Skills in Senior High School Level - Husnaini, Husnaini; Iksan, Muhammad; Wiwin, Wiwin (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The purpose of this study was to investigate the factors that contribute to students' English writing anxiety in the Science 11 class at UPT SMAN 11 Luwu. Students' levels and causes of writing anxiety in English are described (cognitive anxiety, somatic anxiety, and avoidance behavior). Descriptive statistics were used for this investigation. Simple random sampling was used to select a sample of 68 students from the population of eleventh-grade students in a science class. The Causes of Second Language Writing Anxiety Inventory (CSLWAI) by Rezaei and Jafari was used to describe the main factors that contribute to students' writing anxiety, and the Second Language Writing Anxiety Inventory (SLWAI) by Cheng was used to analyze students' anxiety levels. SPSS version 22 and Microsoft Excel 2019 were used to find the mean and percentage of the data, respectively. Students who reported high levels of writing anxiety were statistically typical (M=73.06>65). Inadequate writing technique, linguistic difficulties, a lack of practice, and time constraints are also major contributors to students' writing anxieties.